Assessment of cytotoxicity in three tumor cell lines of the fractions attained from the stem bark of salacia crassifolia (mart. ex. schult.) g. dom (celastraceae) (2012)
For millennia humans have been using plants for medicinal purposes to treat, cure, or prevent diseases, including cancer. Brazilian ecosystem has a high diversity of plant species. From this perspective, a species found in the Cerrado, Salacia crassifolia (Celastraceae), was selected, for an initial screening to determine the cytotoxic potential of this species "in vitro". S. crassifolia has been widely used in traditional medicine to treat kidney diseases, chronic cough, headaches, healing, ulcerogenic, and for treatment of malaria. The fractions: hydroalcoholic (SCCcM-W), dichloromethane(SCCcM-D), hexane (SCCcM-H) and ethyl acetate (SCCcM-A) from the stem bark were tested for cytotoxicity "in vitro" to within MDA -MB-435(melanoma), HCT-8 (human-colon), and SF-295 (CNS) using the MTT colorimetric method. The hexane (SCCcM-H) and ethyl acetate (SCCcM-A) fractions were those that provided significant cytotoxicity against analyzed tumor cells.